Assessment of the Suitability of Methods for Testing the Antioxidant Activity of Anti-Aging Creams - Belma Imamović; Irmela Ivazović; Amra Alispahić; Ervina Bečić; Mirza Dedić; Armina Dacić (Applied Sciences, 2021)
Anti-aging cosmetics are often sought after in order to slow down the aging process. Free radicals are one of the main causes of skin aging, and therefore antioxidants are used in anti-aging cosmetics. The aim of this study was to investigate which method is the most suitable for determining the antioxidant capacity of these products. Having samples extracted, the antioxidant capacity of the extracts obtained was determined by the following spectrophotometric methods: DPPH, Folin-Ciocalteu, FRAP, the ABTS method and the ferroion chelation method with ferrosine. The antioxidant capacity of the samples varied depending on the extract type and the method used. DPPH and ferroion chelation measurements with ferrosine were carried out in the part of the spectrum where plant pigments absorb. These pigments are often found in anti-aging products affecting these methods measurement results. The Folin-Ciocalteu method is suitable for researching the antioxidant capacity of hydrophilic extracts, but not lipophilic ones, where turbidity and the formation of a gelled ring occur. The FRAP method revealed similar results for all the samples and proved to be less sensitive than the others. The ABTS method for both types of extracts has proven to be the most suitable and sensitive method for determining the antioxidant capacity of anti-aging products.